Penerapan Teknik Rotoscoping Sudut 360 Derajat pada Animasi 2D Menggunakan Toon Boom Harmony - Mangkuto, Ifraweri Raja; Bernadhed; Santoso, Joko Dwi (Politeknik Negeri Batam, 2025)
In this digital era, modern animation has developed as a discipline that integrates elements of art and technology. As an art form, animation is based on fundamental principles that serve as the foundation of its knowledge, such as slow in–slow out, squash and stretch, anticipation, to staging. Technological advancements have further enriched these principles and led to the emergence of various animation techniques, one of which is rotoscoping, first introduced by Fleischer Studio in 1917. The rotoscoping technique allows animators to replicate human movements precisely by tracing over live-action footage, resulting in animation with a high level of smoothness and accuracy. Along with the development of visual needs, the Motion Capture technique has emerged, capable of recording movements in a 360-degree angle, although its implementation has cost and equipment limitations. In the context of 2D animation, the development of software such as Toon Boom Harmony provides solutions through features that support effective rotoscoping applications, including onion skinning, timeline flexibility, and vector layering. This study focuses on the application of 360-degree rotoscoping techniques in 2D animation, emphasizing aspects of perspective, lighting, and shadow to create the illusion of realistic depth. Based on the results of a questionnaire with 10 respondents, the 360-degree rotoscoping technique achieved an overall percentage score of 78.89%, categorized as good.